Elevational variability in the fractal structure of the root system of Kobresia tibetica in alpine peat swamp - Wang, Suhong; Zhao, Chengzhang; Wu, Xianshi; Huang, Chenglu; Liu, Dingyue; Zhang, Peixian; Li, Geyang (Rhizosphere, 2023)
Root fractal structure is the result of the phenotypic plasticity of plant root conformation in response to environmental heterogeneity, which can reflect the adaptation strategy of plants to the external environment. Four altitudinal gradients of 3400 m, 3500 m, 3600 m, and 3700 m were selected as experimental sites in Gahai Wetland on the Ruoerge Plateau. Additionally, the Win-RHIZO root analyzer and the standardized major axis estimation (SMA) method were employed to examine the fractal structure of Kobresia tibetica root system at various elevations in the alpine peat swamp. The results showed that the height, density, aboveground biomass, soil water content of the wetland community, as well as the fractal dimension of Kobresia tibetica root system decreased gradually with the increase of altitude, whereas the fractal abundance of Kobresia tibetica root system gradually grew. Kobresia tibetica root fractal dimension and fractal abundance at the 3400 m and 3700 m sites are in a very significant negative correlation between the sample area (p < 0.01), in the land of 3500 m and 3600 m sample was a significantly negative correlation between (p < 0.05). Meanwhile, there is a “shift” between both trade-off relationships. There were elevational differences in the allometric growth relationship between root fractal dimension and root fractal abundance. At the 3400 m sample location, Kobresia tibetica root fractal structure’s regression equation’s SMA slope was <−1, suggesting that the root fractal dimension’s growth rate was greater than the fractal abundance’s growth rate. The SMA slope of the regression equation for the fractal structure of the root system at the 3700 m sample site was >−1, suggesting that the growth rate of Kobresia tibetica root system’s fractal dimension was slower than that of its fractal abundance. Furthermore, at the 3500 m and 3600 m sites, the development rates of fractal dimension and fractal abundance of Kobresia tibetica roots were similar. As the altitude rises, the root system of Kobresia tibetica changes from “dense” to “diffuse”, illustrating how populations of alpine peat swamp plants have ecologically adapted to habitat stress.